1998
DOI: 10.1164/ajrccm.157.1.9609126
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which COPD Affects Exercise Tolerance

Abstract: In view of the recent advances in our understanding of the pathophysiology of COPD, we felt that it would be appropriate to examine the contribution of several abnormalities, not hitherto examined, to exercise limitation in this disease. These included: (1) The ability to exceed maximum expiratory flow (determined during forced maneuvers from TLC) during partial expiratory maneuvers. This is referred to as deltaFEV1. (2) Shape of the flow-volume curve (Shape). (3) Susceptibility to develop dynamic hyperinflati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 22 publications
4
51
0
5
Order By: Relevance
“…The six-minute walk test (TC6') has been used in the dynamic evaluation of the COPD patients, in an attempt to express the exercise capacity. In this test, the distance completed is used as the main parameter for performance evaluation 3,4 . In the stair climbing test (SCT), the work against gravity and the use of muscular groups not frequently used in the daily life makes the metabolic and ventilatory demands more intense, with maximal thresholds being frequently reached in parameters such as heart rate (HR), systemic blood pressure (BP), scores of dyspnea perception and oxygen saturation, measured by wrist oximetry (SpO 2 ) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The six-minute walk test (TC6') has been used in the dynamic evaluation of the COPD patients, in an attempt to express the exercise capacity. In this test, the distance completed is used as the main parameter for performance evaluation 3,4 . In the stair climbing test (SCT), the work against gravity and the use of muscular groups not frequently used in the daily life makes the metabolic and ventilatory demands more intense, with maximal thresholds being frequently reached in parameters such as heart rate (HR), systemic blood pressure (BP), scores of dyspnea perception and oxygen saturation, measured by wrist oximetry (SpO 2 ) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Emphysema causes decreased lung elastic recoil, which increases expiratory airflow resistance and leads to dynamic hyperinflation. [1][2][3] During exercise, dynamic hyperinflation progresses rapidly, decreasing chest wall compliance and impairing respiratory muscle function. [3][4][5][6][7][8][9] Dynamic hyperinflation and an elevated work of breathing precipitate breathlessness, thereby decreasing exercise tolerance and quality of life.…”
mentioning
confidence: 99%
“…In most previous studies, it was found that forced expiratory volume in one second (FEV1) was a poor predictor of exercise capacity [1±3]. Recently, however, it has been shown that indices related to dynamic hyperinflation, such as the inspiratory capacity (IC), are more closely related to exercise tolerance than FEV1 [4,5].Even at rest, patients with COPD often exhibit tidal expiratory flow limitation (FL) [6,7], promoting an increase in end-expiratory lung volume (EELV) due to dynamic hyperinflation with a concomitant decrease in inspiratory capacity and inspiratory reserve volume (IRV) [8,9]. During exercise, normal subjects increase the tidal volume (VT) at the expense of both the IRV and the expiratory reserve volume [8,9].…”
mentioning
confidence: 99%
“…In most previous studies, it was found that forced expiratory volume in one second (FEV1) was a poor predictor of exercise capacity [1±3]. Recently, however, it has been shown that indices related to dynamic hyperinflation, such as the inspiratory capacity (IC), are more closely related to exercise tolerance than FEV1 [4,5].…”
mentioning
confidence: 99%